2018
DOI: 10.1111/1744-9987.12714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin D Receptor Gene Polymorphism on Chronic Renal Failure Susceptibility

Abstract: Our pooled analysis aimed to assess the impact of vitamin D receptor (VDR) gene polymorphism on chronic renal failure (CRF) susceptibility. Relevant studies were searched from multiple databases, then pooled-analyses were performed using Stata software. Eighteen studies involving 2512 CRF patients and 3630 healthy controls were included. Pooled analysis showed that VDR ApaI and TaqI gene polymorphism were not associated with CRF susceptibility either in Asian or in Caucasians populations, and VDR BsmI and FokI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…VDR FokI SNP is closely associated with renal dysfunction in IgAN patients, which also supported the concept that genetic factors play an important role in IgAN renal function and progression. A previous study has shown that VDR FokI polymorphism is associated with risk of CRF in Asians (Li et al, 2018), which is also supported by our findings.…”
Section: Discussionsupporting
confidence: 92%
“…VDR FokI SNP is closely associated with renal dysfunction in IgAN patients, which also supported the concept that genetic factors play an important role in IgAN renal function and progression. A previous study has shown that VDR FokI polymorphism is associated with risk of CRF in Asians (Li et al, 2018), which is also supported by our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Current data is also in harmony with the theoretical perspectives of Li Li et al, who mentioned that there was no association between FokI VDR gene polymorphism and chronic renal failure in the dialyzed ESRD patients without T2DM of Caucasian populations [20] . That may be due to the risk of chronic renal failure and ESRD increased in the presence of other chronic diseases such as diabetes mellitus (DM) which increased in the case of single nucleotide polymorphism of FokI VDR causing a change in the length of amino acid sequence producing FokI single nucleotide polymorphism and increasing (f) allele.…”
Section: Discussionsupporting
confidence: 77%
“…The most common forms of vitamin D receptor (VDR) gene single‐nucleotide polymorphisms are ApaI , BsmI , FokI , and TaqI . It has been shown that vitamin D receptor BsmI and FokI gene polymorphisms are statistically associated with CKD risk . Therefore, the assay levels and VDR polymorphisms may also affect the results in our meta‐analysis.…”
Section: Discussionmentioning
confidence: 98%